Análise da cobertura da Classificação Internacional de Funcionalidade, Incapacidade e Saúde em instrumentos de avaliação do desenvolvimento motor de crianças em Centros de Educação Infantil: um estudo metodológico - Silva, Ewerton Oliveira da (2025)
Introduction: The International Classification of Functioning, Disability and Health (ICF), based on the WHO's biopsychosocial model, seeks to understand the individual's functioning in an integrated way, considering more than just biological factors. In child motor development, this approach converges with current theories, highlighting the importance of Early Childhood Education Centers (ECEC) in the acquisition of motor skills during early childhood. Integrated approaches are fundamental to this development. Objective: To analyze the distribution of the coverage of the ICF components in the motor development assessment instruments for children in ECECs. Method: This is a two-part methodological study. The first part consisted of an integrative review conducted in the PUBMED, LILACS and EMBASE databases, using descriptors related to “Child Development” and “Day Care Centers”. No time limitations were applied, and studies published in Portuguese, English or Spanish that presented evaluative measures of children's motor development in ECECs were included. The second part of the study was based on the analysis of five instruments for assessing the motor development of children in ECECs that were found in the previous stage: Alberta Infant Motor Scale (AIMS), Bayley Scale of Infant and Toddler Development (BAYLEY-III), Test of Gross Motor Development (TGMD-2), Affordances in the Home Environment for Motor Development (AHEMD) and Denver Developmental Screening Tests (DENVER-II). The items of these instruments were linked to the components of the ICF, considering the first level classifications and the second level categories, according to the protocol established by Cieza et al. (2016). Results: Between 2004 and 2021, there was a predominance of the biopsychosocial model in the articles that assessed the motor development of children in ECECs, with 81.82% of the studies analyzed using this approach to interpret the results. 107 concepts were linked to the first level of the Body Functions and Structures component and 240 to the Activity and Participation component. 30 concepts from the first level were linked to the Environmental Factors component. At the second level, 10 categories were linked to Body Functions and Structures, 22 to Activity and Participation and 10 to Environmental Factors in the instruments analyzed. Conclusion: There is a predominance of the biopsychosocial health model. However, there is still a prevalence of categories linked to the Body Functions and Structures and Activities and Participation components, compared to the Environmental Factors component, showing a gap in the understanding of functioning as a dynamic and contextual phenomenon.